Study of temporal intuitionistic fuzzy metric space - Ram Milan Singh (Journal of Hyperstructures)
In order to create a dynamic measure that describes distances between spatiotemporal points whose positions changeover time as well as between the data represented by these points,a temporal intuitionistic fuzzy metric space is created in this pa-per. The notions of temporal fuzzy t-norm, temporal fuzzy t-conorm, and temporal fuzzy negation which have not previously been discussed in the literature are defined, and some of their fun-damental characteristics are investigated, in order to define this new method.The idea that the degrees of nearness and non-nearness change with time is the basis for a novel definition of the concept of temporal intuitionistic fuzzy metric spaces. However, the basictopological characteristics of the temporal intuitionistic fuzzy met-ric space are also looked at. We demonstrate how this new temporal metric space preserves the basic characteristics offered by both clas-sical and fuzzy metric spaces. As a result, a new, more flexible, and dynamic metric topology is created while maintaining the fundamental topological characteristics of fuzzy and intuitionistic fuzzy metric spaces.